2021
DOI: 10.18632/aging.202495
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic potential of cardiac structural and functional parameters and N-terminal propeptide of type III procollagen in predicting cardiac fibrosis one year after myocardial infarction with preserved left ventricular ejection fraction

Abstract: The aim of the study were to evaluate the prognostic potential of serum level of N-terminal propeptide procollagen type III (PIIINP) and heart parameters for predicting heart cardiac fibrosis 1 year after ST-segment elevation myocardial infarction (STEMI) with preserved left ventricular ejection fraction (LVEF). 68 patients with STEMI and preserved LVEF with acute heart failure of the I-III degree according to the Killip classification were examined. Echocardiography was performed and PIIINP levels were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…PIIINP is cleaved from type III procollagen during type III collagen synthesis and degradation, thus reflecting type III collagen turnover 43 . Elevated PIIINP is associated with myocardial fibrosis, 44,45 diastolic dysfunction, 46 and overall poor outcomes in heart failure and other cardiovascular diseases 47,48 …”
Section: Discussionmentioning
confidence: 99%
“…PIIINP is cleaved from type III procollagen during type III collagen synthesis and degradation, thus reflecting type III collagen turnover 43 . Elevated PIIINP is associated with myocardial fibrosis, 44,45 diastolic dysfunction, 46 and overall poor outcomes in heart failure and other cardiovascular diseases 47,48 …”
Section: Discussionmentioning
confidence: 99%
“…A large number of related studies are needed for further exploration in the future. MRA have shown to affect circulating levels of biomarkers indicating cardiac fibrosis and function such as MMP, PIIINP, and NT-pro BNP [19,25,[36][37][38][39][40]. Therefore, 9 Cardiovascular Therapeutics we call for further investigation on noninvasive indicators in response to MRA to prove its predictive value in cardiac remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…However, the correlation of P1CP with cardiac fibrosis extent has to be demonstrated, and it must be noted that P1CP circulating levels may be modulated by other non-fibrotic or non-cardiac processes. Assessing peptides associated with collagen synthesis alone does not seem to constitute a sufficient strategy to specifically detect cardiac fibrosis [ 112 , 113 ]. In a multiparametric approach combining PICP, PIIINP, cardiac fibrosis area determination, and imaging on dilated cardiomyopathy biopsies, a study reported that P1CP/LGE combination provided a sensitive tool to predict adverse cardiac outcomes and that patients positive for cardiac fibrosis presented higher levels of P1CP and LGE [ 112 , 113 , 114 ].…”
Section: Emerging Techniques For the Detection Of Cardiac Fibrosismentioning
confidence: 99%